Editorial: Volume 2 - Bintliff, John (Journal of Greek Archaeology, 2017)
This issue maintains our mission to publish across the whole time range of Greek Archaeology, with articles from the Palaeolithic to the Early Modern era, as well as reaching out from the Aegean to the wider Greek world. Lithics and Ceramics are accompanied by innovative Art History and Industrial Archaeology. Our book reviews are equally wideranging. Our authors are international, and include young researchers as well as longestablished senior scholars. I am sure you readers will find a feast of stimulating studies and thoughtful reviews.